Communication between parents and their adult children’s value system - Komorowska-Pudło, Marta; Sameluk, Agnieszka (Kwartalnik Naukowy Fides et Ratio, 2022)
The value system of every human being, i.e. what is valuable and most important to them, is closely related to the quality of their functioning. This paper presents an analysis of selected family determinants of shaping the value system in young adults. For this purpose, a study was conducted among 252 men and 252 women and it was determined to what extent the quality of the marital communication of parents (measured by the Marriage Communication Questionnaire by Maria Kaźmierczak and Mieczysław Plopa), assessed retrospectively by them, is related to the choice of their preferred values ​​described by Max. Scheler. The research only to some extent confirmed this relationship. They show that the higher the respondents rated the quality of their parents' marital communication, the more often they chose the most important moral values, and depending on their gender, also the values ​​of truth, aesthetic, secular and religious ones.